Two-phase flow separation in axial free vortex flow. (September 2017) - Aghaee, Mohammad; Ganjiazad, Rouhollah; Roshandel, Ramin; Ashjari, Mohammad Ali
Multi-phase flows, particularly two-phase flows, are widely used in the industries, hence in order to predict flow regime, pressure drop, heat transfer, and phase change, two-phase flows should be studied more precisely. In the petroleum industry, separation of phases such as water from petroleum is done using rotational flow and vortices; thus, the evolution of the vortex in two-phase flow should be considered. One method of separation requires the flow to enter a long tube in a free vortex. Investigating this requires sufficient knowledge of free vortex flow in a tube. The present study examined the evolution of tube-constrained two-phase free vortex using computational fluid dynamics. The discretized equations were solved using the SIMPLE method. It was determined that as the liquid flows down the length of the pipe, the free vortex evolves into combined forced and free vortices. The tangential velocity of the free and forced vortices also decreases in response to viscosity. It is shown that the concentration of the second discrete phase (oil) is greatest at the center of the pipe in the core of the vortex. This concentration is at a maximum at the outlet of the pipe.